The Effect of Managerial Ownership and Institutional Ownership on Financial Performance of Technology Sector Companies Listed on the IDX in 2022-2024 - Nidia Anggreni Das; Rowiyah Asengbaramae; Dilla Ramadhani Fitri; Nadia Ananda Putri; Oriza Sativa; Puji Defani Putri; Qurratun Aini (Rescollacom (Research Collaborations Community), 2026)
This study aims to analyze the effect of managerial ownership and institutional ownership on the financial performance of technology sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Managerial and institutional ownership are considered as corporate governance mechanisms that may influence the effectiveness of decision-making and resource allocation within a company. Financial performance is measured using Return on Assets (ROA) to assess the efficiency of asset utilization in generating profits. This research employs a quantitative method with an associative approach. Data were obtained from the annual financial reports of technology companies listed on the IDX for the 2022–2024 period. The data analysis was conducted using multiple linear regression to examine the partial and simultaneous effects of ownership structure on financial performance. The results indicate that both managerial ownership and institutional ownership have a positive relationship with financial performance. However, these relationships are not statistically significant. Managerial ownership, although showing a positive coefficient, does not significantly influence ROA, and the same applies to institutional ownership, whose impact remains weak, possibly due to the lack of active monitoring from institutional investors. These findings suggest that ownership structure alone is insufficient to explain variations in financial performance within technology companies. Other factors such as company size, leverage, innovation, and operational efficiency may play a more dominant role. Therefore, future research should consider incorporating these additional variables to obtain a more comprehensive understanding. This study highlights the need for enhanced corporate governance practices, particularly active oversight from institutional investors, to improve company performance.